The Influence of Auditor Opinion, Key Audit Matters, and Company Performance on Investor Considerations in Investment Decision-Making for Companies Listed on the Indonesia Stock Exchange - Sofian Tambunan, Baktiar (Journal Research of Social Science, Economics, and Management, 2024)
The study aims to determine the impact of auditor opinions, key audit matters, and company performance on investment decisions, motivated by the need for audited financial statements for investors. Auditor opinion reflects whether the financial statements are prepared in all material aspects according to applicable financial reporting standards, and whether the auditor has obtained reasonable assurance that they are free from material misstatement. Key Audit Matters are those considered most significant by the auditor in the current audit period. Financial performance indicators to determine whether a company's operations over a specific period have incurred a loss, one can refer to the income statement. Profitability is the net result of a series of policies and decisions. A high level of profitability which investors use to assess company growth. The research employs a quantitative approach with literature review and questionnaires for data collection, using purposive sampling of investors in companies listed on the Indonesia Stock Exchange (IDX). The hypothesis is tested using Multiple Linear Regression Analysis at a 5% significance level.